Correlates and Consequences of Father Nurturance in an African American College Sample. (June 2015) - Doyle, Otima; Pecukonis, Edward V.; Lindsey, Michael A.
The objectives of the present study are to identify sociodemographic factors associated with father nurturance and assess the relationship between parental (mother and father) nurturance and youth psychological well-being among 216 African American college-aged youth. Participants attended a historically Black college in the Mid-Atlantic region. Findings indicated that the frequency and duration of the participants' interactions with their fathers were associated with levels of father nurturance. Youth whose mothers and fathers were married or cohabitating, compared with those who were separated, divorced, widowed, or never married, had lower levels of psychological well-being. Furthermore, youth who reported more mother nurturance had higher levels of overall psychological well-being. These findings highlight the importance of time-based variables in youths' perceptions of father nurturance and raise important questions about how the nature of the coparental relationship and variations in the fathering role affect youth well-being.